Lifestyles, Social and Family Variables and their Association with Overweight and Obesity in Adolescents - Bei Chen; Marlene Ferrer Arrocha; Georgia Díaz-Perera Fernández; Jorge Bacallao Gallestey (Revista Finlay)
Foundation: obesity is a chronic disease of multifactorial ethology. The family context, parents and other relatives have a great influence on children, modeling their customs, habits, patterns of behavior, eating and physical activity. Objective: to describe the association of lifestyles and social and family variables with overweight/obesity in adolescents. Methods: a cross-sectional descriptive study was carried out, carried out from June 2023 to June 2024, in six polyclinics in Havana, selected by feasibility. 343 adolescents from 10 to 19 years old were included. The dependent variable was overweight/obesity and the independent variables were lifestyle and social and family variables. Absolute and relative frequencies were calculated to characterize the studied population. The associations between the variables were measured using the contingency coefficient. Results: 22.4 % of the adolescents were overweight/obese. The variables related to lifestyles reveal the highest frequency in adolescents who reported not consuming fruits or vegetables. Physical activity had an inverse correlation, with a decrease in the frequency of overweight/obesity as the intensity increased and in those who consumed electronic screens for more than two hours. The highest frequencies of overweight/obesity were recorded in adolescents from small families, with ontogenesis in the “extensive” classification and in mothers aged 19 to 34 years. Conclusions: overweight/obesity in adolescents had a greater association with physical activity and family size.